Prof. Rubish V.M. celebrate 70 anniversary - PCSS, Editorial Team (Physics and Chemistry of Solid State, 2025)
Head of the Uzhhorod Laboratory of Optoelectronics and Photonics Materials of the Institute of Information Registration Problems of the NAS of Ukraine; Doctor of Physical and Mathematical Sciences, Professor; Member of the Organizing Committee of the International Freik Conferences on Physics and Technology of Thin Films and Nanomaterials; Member of the Editorial Board of the Scientific Journal "Physics and Chemistry of Solid State"